2017
DOI: 10.1126/sciadv.aao1595
|View full text |Cite
|
Sign up to set email alerts
|

Origami lattices with free-form surface ornaments

Abstract: We introduce folding strategies to fabricate lattice structures with arbitrarily complex surface (nano-) ornaments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 54 publications
0
47
0
Order By: Relevance
“…Despite the advances in micro/nanofabrication techniques, it is very challenging to create nanopatterns on 3D-shaped devices as the current patterning techniques are mostly only applicable to flat surfaces. Novel strategies have been therefore proposed to create 3D structures from flat sheets that are first ornamented with nanopatterns and are then (self-)folded into complex 3D shapes using origami-based approaches [31]. This could be promising for translating bactericidal and osteogenic nanopatterns to clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the advances in micro/nanofabrication techniques, it is very challenging to create nanopatterns on 3D-shaped devices as the current patterning techniques are mostly only applicable to flat surfaces. Novel strategies have been therefore proposed to create 3D structures from flat sheets that are first ornamented with nanopatterns and are then (self-)folded into complex 3D shapes using origami-based approaches [31]. This could be promising for translating bactericidal and osteogenic nanopatterns to clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…on cell attachment, proliferation, and differentiation, as well as bacterial adhesion and motility, revealing the fact that both eukaryote and prokaryote cells could sense the surface topography at both micro-and nano-scales [28][29][30]. Due to the recent advances in micro-and nano-fabrication techniques, it is now feasible to produce surfaces with arbitrarily complex and precisely controlled surface nanotopography, also known as nanopatterns [29,[31][32][33]. It has been shown that nanopatterns are powerful tools for directing the stem cell fate [34].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotopography describes the structural features such as nanopatterns, nanopores, or surface topography which enhance osteoinductivity and osteointegration of scaffolds [6]. Cell fate and differentiation are influenced by specific nanotopography structures [137]. Different lattices, made by repeats of identically sized and shaped cells, were tested by unfolding through the flattening of the cells.…”
Section: Cv-tebg and Nanotechnology-related Scaffoldsmentioning
confidence: 99%
“…Furthermore, development of nano-fabrication techniques, that allow for decorating the surface of 3D printed biomaterials with such nanoscale topographies, is technologically challenging, particularly when trying to apply nano-topographical features to topologically ordered volume-porous biomaterials. A combination of origami techniques and self-folding techniques [ 37 ] has been recently proposed as a possible way to approach this problem, by folding the porous biomaterials from a flat surface. The research into foldable biomaterials is, nevertheless, at its fancy, and requires many further developments.…”
Section: Bio-functionalizationmentioning
confidence: 99%